(untitled) (Plant Tissue Culture and Biotechnology, 2021)
Nauclea diderrichii is a tree species of economic importance. However, its plantation establishment is limited by inadequate seedling production. Hence, there is ample scope of tissue culture for its mass propagation. Its in vitro plantlets development as affected by media strengths indicated that 100 % seed germination was obtained in full MS basal medium while the least (3.35 %) was from quarter-strength at 8 Weeks after inoculation (WAI). The effects of BAP and NAA assessed on the growth of its sub-cultured plantlets showed that highest number of leaves (17) and adventitious shoots (3) were obtained from MS basal medium supplemented with 0.1 mg/l BAP only. Whereas, highest shoot length (3.61 cm) and average number of roots (5/plantlet) were obtained from the same medium without hormone(s) at 8 WAI. Further sub-culturing into MS with 0.05 mg/l NAA resulted into plantlets having optimum shoot and massive root growth ready for acclimatization in 6 WAI. The plantlets were successfully acclimatized using coconuthusk/ topsoil mixture with 90 % survival. Plant Tissue Cult. & Biotech. 31(1): 51-60, 2021 (June)